Effect of rice starch on the linear expansion of fish crackers (keropok) - Yu, Swee Yean (John Wiley & Sons, 1993)
Fish crackers containing a ratio of tapioca starch rice starch of 80:20 were acceptable in terms of linear expansion. Any further increase in the concentration of rice starch into the formulation resulted in an unacceptable level of expansion. The reduced expansion has been related to the viscoelastic nature and cross-linking ability of rice proteins.